Stop and play digital health education intervention for reducing excessive screen time among preschoolers from low socioeconomic families: cluster randomized controlled trial - Raj, Diana; Ahmad, Norliza; Mohd Zulkefli, Nor Afiah; Lim, Poh Ying (JMIR Publications, 2023)
Background: High prevalence of excessive screen time among preschool children is attributable to certain parental factors such as lack of knowledge, false perception about screen time, and inadequate skills. Lack of strategies to implement screen time guidelines, in addition to multiple commitments that may hinder parents from face-to-face interventions, demands the need to develop a technology-based parent-friendly screen time reduction intervention. Objective: This study aims to develop, implement, and evaluate the effectiveness of Stop and Play, a digital parental health education intervention to reduce excessive screen time among preschoolers from low socioeconomic families in Malaysia. Methods: A single-blind, 2-arm cluster randomized controlled trial was conducted among 360 mother-child dyads attending government preschools in the Petaling district, who were randomly allocated into the intervention and waitlist control groups between March 2021 and December 2021. This 4-week intervention, developed using whiteboard animation videos, infographics, and a problem-solving session, was delivered via WhatsApp (WhatsApp Inc). Primary outcome was the child’s screen time, whereas secondary outcomes included mother’s screen time knowledge, perception about the influence of screen time on the child’s well-being, self-efficacy to reduce the child’s screen time and increase physical activity, mother’s screen time, and presence of screen device in the child’s bedroom. Validated self-administered questionnaires were administered at baseline, immediately after the intervention, and 3 months after the intervention. The intervention’s effectiveness was evaluated using generalized linear mixed models. Results: A total of 352 dyads completed the study, giving an attrition rate of 2.2 (8/360). At 3 months after the intervention, the intervention group showed significantly reduced child’s screen time compared with the control group (β=−202.29, 95 CI−224.48 to −180.10; P<.001). Parental outcome scores also improved in the intervention group as compared with that in the control group. Mother’s knowledge significantly increased (β=6.88, 95 CI 6.11-7.65; P<.001), whereas perception about the influence of screen time on the child’s well-being reduced (β=−.86, 95 CI −0.98 to −0.73; P<.001). There was also an increase in the mother’s self-efficacy to reduce screen time (β=1.59, 95 CI 1.48-1.70; P<.001) and increase physical activity (β=.07, 95 CI 0.06-0.09; P<.001), along with reduction in mother’s screen time (β=−70.43, 95 CI −91.51 to −49.35; P<.001). Conclusions: The Stop and Play intervention was effective in reducing screen time among preschool children from low socioeconomic families, while improving the associated parental factors. Therefore, integration into primary health care and preschool education programs is recommended. Mediation analysis is suggested to investigate the extent to which secondary outcomes are attributable to the child’s screen time, and long follow-up could evaluate the sustainability of this digital intervention.